Hydrology of Basin of Barada Ali Valley Northeast of Diyala - Falih, Hiam N. (Al-Adab Journal, 2021)
Basin of Barada Ali Valley is one of the seasonal valleys, its area 73.9 km2. The study aims to demonstrate the hydrological characteristics are represented by the size of the surface runoff of Barada Ali Basin. Which flows into Qara Tu River in northeastern of Diyala Governorate. She has used (scs-cn) models, which is the most widely used method for estimating the depth of runoff. Which deals with many variables including land cover, soil hydrology and quantities of rainfalls and HEC-HMS model. This model was worked on within the environment of geographic information systems and remote sensing techniques, in the creation of a geographic database with morphometric and hydrological characteristics for Valley of Barada Ali basin. The study concluded the hydrological significance of Barada Ali valley basin through rise of CN values. Where the weighted cn curve for the basin reached 78, as for the volume of surface runoff (QV). It has reached the highest amount in the lower parts of the basin that ranged between 3980-10900 M3 with an area of ​​(26.5) km2 of the total area of ​​the basin. Then the hydrograph of the drainage curve of the basin was obtained based on the analysis of space rain data for the period (2018-2019). Where it reached the highest peak of the flow of Barada Ali Basin by (29.63 m3 / s). This means that the amount of water discharged outside the basin during (177) minutes is estimated at (1062.23) M3. This amount indicates a decrease in the volume of runoff, the reason for this is due to the characteristics of the basin that allow to leak large quantities of falling water during the period of the rainstorm. The losses amounted to about (2957.93) M3 of the total precipitation which is estimated at (4020.16) M3 and the remainder represents surface runoff.